Advancing human development theory and practice - Stewart, Frances 1940-; Ranis, Gustav; Samman, Emma 1971- (Oxford Oxford University Press, 2018)
Human Development has been advocated as the prime development goal since 1990, when the publication of the first UNDP Human Development Report proposed that development should improve the lives people lead in multiple dimensions instead of primarily pursuing economic growth. This approach forms the foundation of 'Advancing Human Development: Theory and Practice'. It traces the evolution of approaches to development, showing how the Human Development approach emerged as a consequence of defects in earlier strategies. 'Advancing Human Development argues that Human Development' is superior to measures of societal happiness. It investigates the determinants of success and failure in Human Development across countries over the past forty years, taking a multidimensional approach to point to the importance of social institutions and social capabilities as essential aspects of change. It analyses political conditions underlying the performance of Human Development, and surveys global progress in multiple dimensions such as life expectancy, infant mortality, and education and outcomes, whilst reflecting on dimensions which have worsened over time, such as rising inequality and declining environmental conditions. These deteriorating conditions inform 'Advancing Human Development' its account of the challenges to the Human Development approach, covering the insufficient attention paid to macroeconomic conditions and the economic structure needed for sustained success.
Includes bibliographical references (pages 237-266) and indexes.
Electronic reproduction.
Keywords: Economic development; Electronic books